Methodologies of the Validation of Software Architectures - Amina El Murabet; Anouar Abtoy (Universitas Dian Nuswantoro, 2023)
Software architecture validation is the process of assessing whether a software architecture meets its intended requirements and goals. It is an important step in the software development process, as it can help to identify and address potential problems early on before they become more costly and difficult to fix. There are a variety of different methodologies that can be used to validate software architecture. Some of the most common methodologies include Architectural evaluation methods, Architecture tests and reviews, and Model-based validation. This paper will provide an overview of the different methodologies that can be used to validate software architecture. Apart from that, it also analyzes and summarizes the strengths and weaknesses of each method so that it can guide determining the most appropriate methodology for a particular case.